Novejša problematika delovnopravnega položaja delavcev v primeru insolventnosti delodajalca - Tičar, Luka (Delavci in delodajalci, 2012)
The legal status of workers in case of insolvency of the employer presents an important area of legal discussions and activities of various stakeholders, including employers, workers, managers, the courts and the state. This way the legislator undoubtedly attempted to respond to the critical economic situation, yet the question remains whether the legislation makes it possible and guarantees a prompt beginning of an insolvency proceeding after insolvencyhas been determined. The success of an individual proceeding and the best possible payment of creditors namely depend to a large extend on the latter. According to the practice, the answer to the question above seems to be negative.
Keywords: delovno pravo; insolventnost; nelikvidnost; odpoved; podjetja; pravice; prisilna poravnava; socialna varnost; stečaj; zaposleni